Prototype of Slotted Microstrip Patch Antenna for Multiband Application - Sharma, Ragini; Kumar Aghwariya, Mahesh; Agrawal, Tanvi; tyagi, Sachin (International Journal of Engineering and Technology, 2018)
In this paper a slotted microstrip patch antenna has been designed that works for two frequencies 1.42GHz and 2.65GHz. Since a microstrip patch antenna works only on one resonant frequency so converting that into a multiband patch antenna would enhance the bandwidth Â and also utilizes the multiple frequencies of operation. This multiband slotted patch antenna is fabricated on FR4 lossy dielectric substrate whose dielectric constant is 4.3 and height is 1.6mm. The length and width of patch are taken as 51.16mm and 39.86mm respectively. we cut out the slots so that the patch antenna works at multiple frequencies. Another advantage of presented design is it reduced the size of antenna actually required for 1.42GHz frequency. Simulation and analysis of slotted patch antenna is done by CST software. Simulation and fabrication results show that the presented antenna design characteristics meet with the standard characteristics of antenna.Â Â